Plasma leptin levels of elite endurance runners after heavy endurance training - Ishigaki, T.; Koyama, K.; Tsujita, J.; Tanaka, N.; Hori, S.; Oku, Y. (Journal of Physiological Anthropology, 2005)
A decrease in testosterone levels and an increase in cortisol levels are observed in male athletes with the overtraining syndrome (OTS). Cortisol causes blood leptin levels to rise and testosterone has an inverse relationship with blood leptin levels. Therefore, we hypothesized that the hormonal changes as a result of OTS induce an increase in leptin. To test this hypothesis, we examined the relationship among changes in leptin, testosterone and cortisol in thirteen male collegiate distance runners (aged 20.3 1.1 years) before and after an 8-day strenuous training camp. Runners ran 284.1 48.2 km during the training camp. Body fat percentages and plasma glucose concentrations decreased significantly after the training. Non-ester fatty acids and total cholesterol concentrations in blood were unchanged. Serum cortisol concentrations showed a significant increase after the training camp (from 11.82 2.00m g/dl to 16.78 3.99m g/dl), and serum testosterone decreased significantly (from 408.0 127.6 ng/dl to 265.2 97.6 ng/dl). The ratio of testosterone to cortisol (TCR) dropped by 50% after training (from 35.62 13.69 to 16.94 8.47). These results suggest that the subjects reached a state of the OTS. Contrary to our hypothesis, plasma leptin was not significantly changed (from 1.34 0.29 ng/ml to 1.49 0.18 ng/ml). D Plasma leptin was not significantly correlated with D serum cortisol, D TCR or D fat percentage. However, D serum testosterone was positively correlated with D plasma leptin (r 596, p 0.05). Plasma leptin concentrations might modulate the secretion of testosterone in overtraining conditions. In conclusion, the change in blood leptin level is independent of the changes in cortisol, TCR and fat percentage in highly trained male athletes in the state of the OTS.